STRATEGI MANAJEMEN PERUBAHAN DAN TANTANGANNYA DALAM MENINGKATKAN KINERJA MANAJEMEN OPERASIONAL “PT XYZ” - Syamsudin; Wahyuddin Wahyu (Jurnal Manajemen, 2026)
Organizational restructuring in operational lines often faces obstacles due to human resource readiness. This study aims to evaluate the implementation of change management strategies, map the challenges faced, and analyze their impact on operational management performance at PT XYZ. The research method used is qualitative with a descriptive case study design. Data collection was conducted through in-depth interviews with eight informants (managers, supervisors, and operational staff), passive participant observation on the production floor, and documentation study of internal company reports. The results indicate that PT XYZ implemented a structured change strategy through Kurt Lewin's three stages: unfreezing (socializing the urgency), changing (intensive training and mentoring by Change Champions), and refreezing (standardizing new SOPs and aligning financial bonuses). The main challenges found include passive resistance from senior employees due to psychological anxiety over automation, communication gaps regarding incentive regulations, and technical lagging on the Enterprise Resource Planning (ERP) system server. The impact on operational performance formed a J-curve pattern; a short-term performance decline occurred at the beginning of the transition, marked by a 14% cost swell and a spike in product defects up to 3.2%. However, after the adaptation phase was reached in 2026, operational efficiency increased significantly, evidenced by a cycle time reduction from 12 to 7.5 minutes, an 18% decrease in production costs, and a drop in the defect rate to 0.6%. In conclusion, a comprehensive and inclusive change management strategy is an absolute prerequisite for boosting the efficiency and flexibility of a company's operational lines.